Diagnostic Performance of Macular Ganglion Cell/Inner Plexiform Layer Thickness to Discriminate Normal Eye from Eye with Early Glaucoma Using Cirrus Spectral-Domain Optical Coherence Tomography - Widya Artini; Baltazar Bimo Bisara (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Background: Glaucoma is a progressive optic neuropathy characterized by a progressive loss of retinal ganglion cells (RGC). In glaucomatous optic neuropathy, structural optic nerve changes may occur before detectable functional loss, which can be diagnosed early by detecting loss of RGC. This review was conducted to see the diagnostic performance of macular ganglion cell/inner plexiform layer (GC-IPL) thickness parameters to discriminate normal eye from early glaucoma eye using Cirrus Spectral-domain OCT compared to peri-papilarry Retinal Nerve Fiber Layer (RNFL) thickness parameters. Methods: Literature search was conducted from MEDLINE database using Pubmed, Clinical Key, and ScienceDirect. No publication date was set, and only articles published in English were included. Reference list from the included studies were also checked for potentially relevant articles. Results: Twenty articles were found related to search term. Seven articles met the inclusion criteria. Fourteen others were excluded. All studies revealed significant thinner GC-IPL and RNFL average thickness in glaucoma patients compared to normal patients. GC-IPL Average was inferior to GC-IPL Minimum and RNFL inferior in determining normal eye from early glaucomatous eyes. Studies evaluating the diagnostic performance of Ganglion Cells Complex (GCC) thickness also found low sensitivity values, ranging between 61.0% and 78.6% for average GCC. Conclusion: Diagnostic performance of GC-IPL is comparable to RNFL parameters measurement in detecting early glaucoma eyes. Best performance in detecting early glaucoma were showed by GC-IPL minimum and RNFL inferior.